The Master of Library Science graduates of the Institute of Library Science, University of the Philippines, AY 1981-1992 a follow-up study - Robles, Ma. Narea Santiago 1967- (1995)
are now holding professional library positions. This supports the second proposition of this study that there is a significant relationship between the possession of an MLS degree and the graduates' access to career opportunities. As to the extent with which the MLS program has prepared the graduates for their present job, more than half (65 or 52.85) of the respondents answered they were prepared "extremely well."
graduates were promoted in rank and in salary since they obtained the MLS degree and 109 (88.6
respondents are holding professional library positions. This supports the first proposition of this study that a significantly greater number of MLS graduates are employed as librarians/information specialists and are holding professional positions. However, there are still seven respondents with non-professional titles. Only two MLS graduates are in occupations related to library/information work; they are library educators.
All the knowledge acquired from the courses included in the MLS program have been applied by the graduates in their present jobs, and thus considered useful. "Organization of Library and Information Resoruces I" (formerly Organization of Library Materials) and "Introduction to Information Science", "Research Methodology," "Organization of Library and Information Resources II" (formerly Advanced Cataloging), "Information Technology," and "Information System Analysis and Design" are courses which are considered very useful.
Based on these findings, it is reasonable to conclude that the MLS program has improved in preparing the graduates for their present positions. To determine the factors accountable for the significant improvements, the MLS program was academically evaluated and the graduates' degree of satisfaction with the program was also examined.
Eighty-five (69.1
In conclusion the MLS program, in terms of its curricular offerings, is appropriate and helpful in preparing the graduates for their present job or previous jobs in librarianship. A large number of the graduates prove to be highly satisfied with the curricular offerings and the MLS programs as a whole.
It was found out that 95.93 percent of the respondents are now engaged in library/information work. Only five respondents are not in library/information work. Not one of the graduates is unemployed. It was ascertained that 109 (88.6
The descriptive method of research was used and the main data-gathering tool was a questionnaire. Among the 168 graduates from 1981 to 1992 two of whom were listed as dead, 123 or 74.1 percent responded to the survey.
This study sought to determine the status of the 168 Master of Library Science graduates of the Institute of Library Science for the period AY 1980-81 to AY 1991-92 and to compare the results with those of Corazon Monroy's study. This will give a broad picture of the MLS graduates from 1966 to 1992. It is also the aim of the study to find out what types of positions the MLS graduates are holding and what effect the MLS degree program has had on their careers. Moreover, it tries to ascertain what courses taken by these graduates are considered useful or least useful in the performance of their responsibilities.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: University of the Philippines Diliman. -- Institute of Library Science -- Alumni; University of the Philippines Diliman. -- Institute of Library Science -- Graduate students